INTEGRATION OF THEORY AND PRACTICE IN TRAINING ELECTRICIAN SPECIALISTS - Rizoyev Sirojiddin Sano o‘g‘li, (TADQIQOTLAR, 2026)
Abstract This article discusses the importance of integrating theoretical knowledge and practical  skills  in  the  training  of  electrician  specialists  in  vocational  education institutions. Effective professional activity in the electrical field requires students to master  both  the  theoretical  principles  and  practical  skills.  The  study  examines  the interrelation between physics and specialized technical subjects, as well as the role of laboratory  work  and  industrial  practice  in  developing  professional  competencies. Furthermore, the article explores modern pedagogical technologies to strengthen the integration of theory and practice in vocational education.